Pengembangan Sungai Kapuas sebagai Destinasi Wisata Unggulan di Indonesia - Palupi, Santi; Adi, Antonius; Alfadin Nur, Dewa Sagita (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
Indonesian regions have their own characteristics in tourism development, such as the Kapuas River which is a river tourism destination. The Kapuas River offers natural beauty, cultural heritage, local community activities, as well as the experience of enjoying a light meal while taking photos. Even though initial data has been produced through identification and observation, it is still necessary to improve facilities and infrastructure along the Kapuas River to encourage tourism development. This research uses an observational method, recording the history, uniqueness, attractiveness and volume of tourist visits in a certain period. Data was obtained through in-depth interviews and field observations with the participation of the government, community and other stakeholders. A total of 10 competent sources were interviewed to explain the development of the Kapuas River. The research results identified deficiencies in three main aspects: Accessibility, Amenities and Attractions. The development of the Kapuas River destination requires comprehensive improvements, including professional packaging for tourism activities and integration with the tourism industry. The pentahelix role of all stakeholders, such as the government, community and related parties, is the key to fulfilling three main aspects in the development of tourism on the Kapuas River. Keywords: River Tourism, Kapuas River, Community Based Tourism